Optimization of and experimentation with a bifurcated swing tube strip fertilizer spreading device based on MBD-DEM coupling - Dun, Guoqiang; Sheng, Quanbao; Ji, Xinxin; Li, Xin; Wei, Yuhan; Gao, Shang; Zhang, Chaoxia (Frontiers in Plant Science, 2024)
Introduction To improve the utilization rate of fertilizers, realize the precise spreading of fertilizers in controllable strips, and ensure the uniformity of fertilizer spreading in both longitudinal and transversal directions, a bifurcated swing tube fertilizer spreading device driven by a spatial hammer pendulum crank mechanism was designed. Methods First, the drive mechanism was designed based on the cylindrical pair of the mechanism. A mathematical model pendulum equation was used to design the swing tube, and the equation of motion of fertilizer particles was established by analyzing the motion and force of fertilizer particles in fertilizer spreading. The dynamic parameters of the fertilizer spreading device (nozzle height, forward velocity, and swing frequency) were identified as the test factors affecting the uniformity of fertilizer spreading. Second, the coupling model based on MBD-DEM was established, and the coupling simulation analysis of the fertilizer spreading process was carried out using EDEM-RecurDyn software. Taking the nozzle height, forward velocity, and swing frequency as test factors and the uniformity coefficient of longitudinal and transversal fertilizer spreading as evaluation indexes of the fertilizer discharging effect, we analyzed the influence of a single factor on the indexes. Moreover, the ternary quadratic generalized rotating combination response surface test established the regression equations of three factors and two evaluation indexes. Finally, the simulation and bench test were verified under the optimal combination of parameters and compared with the single swing tube bench test with the same parameter conditions. Results The results of the single-factor test showed that the fertilizer discharge effect was better when the nozzle height was 350.0–450.0 mm, the forward velocity was 0.5–1.5 m/s, and the swing frequency was 1.40–2.00 Hz. The results of the response surface test proved that the nozzle height, forward velocity, and swing frequency all had a highly significant effect on the uniformity coefficient of fertilizer spreading in the longitudinal and transversal directions (P<0.01). Moreover, the optimization concluded that when the nozzle height is 450.0 mm, the forward velocity is 0.5–0.8 m/s, and when the swing frequency is within the range of 1.40–2.00 Hz, the uniformity coefficient of longitudinal fertilizer spreading is ≤25% and the uniformity coefficient of transversal fertilizer spreading is ≤45%. The results of bench validation showed that the errors of longitudinal and transversal fertilizer spreading uniformity coefficients in the bench test were 3.46% and 1.44%, respectively, and the simulation agreed with the bench test. The results of comparative tests showed that the uniformity coefficient of the longitudinal and transversal of the fertilizer spreading device was reduced by 50.33% and 14.95%, respectively, for the bifurcated swing tube compared with that of the single swing tube. It is proved that the bifurcated swing tube strip fertilizer spreading device can achieve the purpose of uniform fertilizer spreading and performs better than the single swing tube in fertilizer spreading. Conclusion The results and methods of this study can provide a reference for the design of swing tube strip fertilizer spreading devices and related fertilizer spreading performance tests.